If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5 + 2(2x + 2) = -4(x + 4) Reorder the terms: 2x + -5 + 2(2 + 2x) = -4(x + 4) 2x + -5 + (2 * 2 + 2x * 2) = -4(x + 4) 2x + -5 + (4 + 4x) = -4(x + 4) Reorder the terms: -5 + 4 + 2x + 4x = -4(x + 4) Combine like terms: -5 + 4 = -1 -1 + 2x + 4x = -4(x + 4) Combine like terms: 2x + 4x = 6x -1 + 6x = -4(x + 4) Reorder the terms: -1 + 6x = -4(4 + x) -1 + 6x = (4 * -4 + x * -4) -1 + 6x = (-16 + -4x) Solving -1 + 6x = -16 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -1 + 6x + 4x = -16 + -4x + 4x Combine like terms: 6x + 4x = 10x -1 + 10x = -16 + -4x + 4x Combine like terms: -4x + 4x = 0 -1 + 10x = -16 + 0 -1 + 10x = -16 Add '1' to each side of the equation. -1 + 1 + 10x = -16 + 1 Combine like terms: -1 + 1 = 0 0 + 10x = -16 + 1 10x = -16 + 1 Combine like terms: -16 + 1 = -15 10x = -15 Divide each side by '10'. x = -1.5 Simplifying x = -1.5
| -x-4y=-29 | | 3x^2-5y^2=23 | | (4x-4xi)=0 | | y-8=21 | | 2x+1/4=54 | | e^2+4ef+3f^2=0 | | 0.50x+0.35(50)=23.5 | | -2.4-y/4=-8.8 | | 5x-14=19x-24 | | 8-3(2t+1)=5(t+2) | | -9=-2+v | | -6x-9=2x+23 | | 7(x-7)+22=5(x-5) | | 17x+6=46-3x | | 5x+5=3+7x-6 | | 8-8x-3=-42+4x-13 | | 55y-3=100 | | 8x-8=8(x+7) | | 6+2(6u-2)=-5(3u-1)+9u | | 12+3/4 | | -1+6(x-4)=12x+3-6x | | 8+5=4+13 | | 5/6x+8 | | -32+k=-26 | | 15x^5/25x | | 2x+1.4=5.1x-15.96 | | 4x-(10-x)=15/7 | | x-3(x-6)=30 | | 10=-2/7y | | -6/5w=-42 | | 3x^2+54+24=0 | | (4x^2+23x+25)/(x+4) |